2018
DOI: 10.17146/jsmi.2018.19.4.4966
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Tensile Properties of Pva/Snail Mucin Nanofiber Membranes

Abstract: MORPHOLOGY AND TENSILE PROPERTIES OF PVA/SNAIL MUCIN NANOFIBER MEMBRANES. Snail mucin has been widely known to contain agents with wound healing properties. A preliminary research with regard to the potential to manufacture composite nanofibrous membranes of polyvinyl alcohol (PVA) and snail mucin (SM) by the electrospinning technique for wound dressing applications has been conducted. The effect of SM concentration on the morphology and tensile properties of PVA/SM nano membrane has been investigated. The PVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This aligns with previous research by [55], which reported a positive correlation between smaller fiber diameter and higher tensile strength. The increased packing density of thinner fibers creates a more robust structure capable of withstanding greater loads [56]. This aligns with the findings from Hartatiek et al [57], who observed a similar inverse relationship between fiber diameter and mechanical properties.…”
Section: Mechanical Propertiessupporting
confidence: 88%
“…This aligns with previous research by [55], which reported a positive correlation between smaller fiber diameter and higher tensile strength. The increased packing density of thinner fibers creates a more robust structure capable of withstanding greater loads [56]. This aligns with the findings from Hartatiek et al [57], who observed a similar inverse relationship between fiber diameter and mechanical properties.…”
Section: Mechanical Propertiessupporting
confidence: 88%
“…Overall, the diameter of the membranes fabricated in this study is comparable to that of the previous studies [20,21], which is in the range of 100-300 nm. It has been reported elsewhere that PVA-SM concentration 0% produced a membrane with fiber diameter, tensile strength, and elastic modulus of 460.17 ± 128.32 nm, 3,48 MPa, and 12.00 MPa, respectively [22].…”
Section: Morphologymentioning
confidence: 78%
“…The tensile testing procedure was prepared in accordance with ASTM D882. The prepared specimen [22] was depicted in Figure 2.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations